Improving moisture resistance in solid-state electrolytes (SSEs) through high entropy effect - Poon, James Hong Pin (Nanyang Technological University, 2024)
The demand for the improvement of lithium batteries grows with the increasing demand for higher energy storage. With the ever present risk of catastrophic damage with misuse and accidents involving liquid electrolytes in lithium batteries, solid state electrolytes offer a comprehensive solution with non-flammability, non-volatility, no liquid leakage, wider cell voltage window and higher energy density. However, solid state electrolytes have problems of their own, with lithium indium chloride lacking moisture stability to be able to operate in atmospheric air without degrading into its components. In this study, the high entropy effect is explored in improving the moisture resistance of lithium indium chloride and maintaining its ionic conductivity. The samples were characterized via XRD and evaluated through EIS and qualitative analysis of the moisture resistance. It is realised that the composition of Li2.7In0.9Mn0.025Zn0.025Zr0.05Cl5.5F0.2 where additive chlorides are mixed in with 90% of sintered lithium indium chloride provides the best trade off in terms of ionic conductivity and moisture resistance. This study explores the method of improving the feasibility of using solid state electrolytes through the high entropy effect in an effort to achieve progress in the commercial use of solid state electrolytes in lithium batteries, providing a safe and better alternative to the current commercial use of liquid electrolytes.